Laparoscopic cholecystectomy under spinal anesthesia in a 5-year-old child: A case report - Hazra, Rajdip; Roymondol, Avijit (Asian Journal of Medical Sciences, 2023)
Symptomatic cholelithiasis in pediatric patients should be dealt with cholecystectomy. Due to its minimally invasive nature, laparoscopic approach is better than conventional open approach. Although safety of spinal anesthesia (SA) in adult laparoscopic surgeries including cholecystectomy is well established, its use in pediatric laparoscopic surgeries is extremely limited with only a few studies being published till date. Here, we report a case of laparoscopic cholecystectomy (LC) in a 5-year-old child which was successfully managed with SA. This may be the very first case report of pediatric LC under SA.